The views of the five schools of thought on the marital marriage of adultery | آراء المذاهب الخمسة في نكاح الحامل من الزنا - Tsuaibah Tsuaibah; Aida Humaira (Fakultas Dirasat Islamiyah, Univitas Islam Negeri (UIN) Syarif Hidayatullah Jakarta, 2017)
This paper deals with the issue of the marriage of a pregnant woman fromadultery as one of contemporary contemporary issues. Marriage of pregnantadultery is one of the issues that provoked a dispute between the scholars of oldand recent, some of them allow the marriage of pregnant adultery, and some ofthem do not permit. Then they differed as to whether the marriage was adulterywith it or not, even the consequences under it. There have been many questionsabout this issue in our contemporary society. In this study, the researcher uses adescriptive approach comparing the views of the scholars in the ruling on themarriage of a pregnant woman with adultery and its effects, especially amongthe five schools of thought. After the analysis and comparison of the scholars'opinions, the researcher concluded that it is permissible to marry a pregnantwoman from adultery with a zina, and that it is permissible for a non-adultererto contract a pregnant woman before adultery before she puts her pregnancy, butit is not permissible for the husband to take her until she puts her pregnancy.Among the effects of this marriage in the child is: In terms of descent, the child isnot attributed to the adulterer by agreement of the jurists if his mother was a bed,and is not attributed to the most likely if his mother is not a bed. In terms ofinheritance, the child does not inherit from the adulterer, nor to the adultererwho is related to the adulterer. In contrast, neither the adulterer nor the child'sheir is inherited, because his ratio is cut off from the adulterer. And theinheritance of the child only from his mother's side, because he is related to it,inherited from it and inherited it and whoever made it. In terms of alimony, thischild should not be obliged to pay zakaah on his father, and the adulterer mustnot pay zina for his son.